Lipid-Based Delivery System for Topical Phenytoin - Siang Yin Lee & , Yeong Yaw Pung, Boon Kuang Khor, Wei En Kong, Cai Ting Tan, Siew Yong Teo (Journal of Applied Pharmaceutical Science, 2016)
The wound healing effect of topical phenytoin has been reported but its effective delivery system is still under-researched. The present work aimed to formulate topical lipid-based gels for effective delivery of phenytoin. Three lipid-based emulsions with different droplet sizes were prepared using coconut kernel oil (CKO) and soybean oil (SBO) blends as an oil phase. Stable lipid-based emulsion with 100% emulsion stability index (ESI) over seven heating/cooling cycles could only be formed when the oil droplet satisfied the nano size criterion, as demonstrated by nano-emulsion. The stability of macro-emulsion and cream could be enhanced by the addition of Aristoflex ammonium acryloyldimethyl-taurate/VP (AVC) copolymer as the gelling agent. These gels, designated as nano-emulgel, macro-emulgel and cream-gel, were subsequently loaded with phenytoin. All gels exhibited non-Newtonian and shear-thinning flow behavior, with high yield stress ranged 18.8 – 51.5 Pa. The in vitro drug release profiles of all formulations followed the first-order kinetic model, with R2 > 0.95. It was found that lipid nano-emulgel demonstrated the highest release rate of phenytoin, with 93.12% drug released in 12 hours, followed by cream-gel with 56.42% and macro-emulgel with 51.51%. CKO/SBO nano-emulgel was identified as the most suitable lipid topical gel formulation for effective delivery of phenytoin.
Keywords: Cream-gel, lipid, macro-emulgel, nano-emulgel, phenytoin, topical.